Prospective, randomised, controlled trial to study the effect of intracoronary injection of verapamil and adenosine on coronary blood flow during percutaneous coronary intervention in patients with acute coronary syndromes. Issue 9 (31st January 2006) - Vijayalakshmi, K; Whittaker, V J; Kunadian, B; Graham, J; Wright, R A; Hall, J A; Sutton, A; de Belder, M A
Abstract : Objectives: To study the impact of injection of verapamil and adenosine in the coronary arteries on TIMI (Thrombolysis in Myocardial Infarction) frame count (TFC) after percutaneous coronary intervention (PCI) in patients with an acute coronary syndrome (ACS). Methods: Prospective, randomised, controlled study of the intracoronary administration of normal saline versus verapamil versus adenosine in patients undergoing PCI in the setting of an ACS, even when flow is visually established to be normal or near normal. Patients were randomised to receive verapamil (n  =  49), adenosine (n  =  51) or normal saline (n  =  50) after PCI. Quantitative angiography, TIMI flow grade (TFG), TFC and myocardial blush grade were assessed before PCI, after PCI and after drugs were given. Wall motion index (WMI) was measured at days 1 and 30. Results: 9 patients in the verapamil group developed transient heart block, not seen with adenosine (p ⩽ 0.001). Compared with saline, coronary flow measured by TFC improved significantly and WMI improved slightly but insignificantly in both the verapamil (TFC: p  =  0.02; mean difference in improvement in WMI: 0.09, 95% confidence interval (CI) 0.015 to 0.17, p  =  0.02) and the adenosine groups (TFC: p  =  0.002; mean difference in improvement in WMI: 0.08, 95% CI 0.004 to 0.16, p  =  0.04). The improvements in TFC and WMI did not differ significantly between the verapamil and the adenosine groups (TFC: p  =  0.2; mean difference in improvement in WMI: 0.01, 95% CI −0.055 to 0.08, p  =  0.7, respectively). Conclusion: Administration of verapamil or adenosine significantly improves coronary flow and WMI after PCI in the setting of an ACS. Flow and WMI did not differ significantly between verapamil and adenosine but verapamil was associated with the development of transient heart block.